Associations of lipids and lipid-lowering drugs with risk of stroke: a Mendelian randomization study - Qin, Hao; Yang, Fan; Zhao, Haitao; Zhao, Jinchuan; Lin, Siyuan; Shang, Yinshuai; Zhang, Chaoling; Hao, Pengfei; Zhang, Xianfeng (Frontiers in Neurology, 2023)
Background: Stroke is a leading cause of death worldwide, but it is unclear whether circulating lipids and lipid-lowering drugs are causally associated with stroke and its subtypes. Methods: We used two-sample Mendelian randomization(MR) to examine the effects of blood lipids and lipid-lowering drugs on stroke and its subtypes. Results: The inverse variance weighted Mendelian randomization (IVW-MR) revealed the low-density lipoprotein cholesterol(LDL-C)(OR, 1.46; 95% CI, 1.17–1.83; p = 0.0008) and apolipoprotein B(apoB)(OR, 1.46; 95% CI, 1.21–1.77; p = 0.0001) was positively correlated with large artery stroke(LAS). However, no causal effect was found in LDL-C and apoB on LAS risk when we conducted mvMR. The IVW-MR also found a suggestive evidence that decreased LDL-C levels mediated by the PCSK9 (proprotein convertase subtilisin-kexin type 9) gene were associated with a reduced risk of any stroke(AS)(OR, 1.31; 95% CI, 1.13–1.52; p = 0.0003), any ischemic stroke(AIS)(OR, 1.29; 95% CI, 1.10–1.51; p = 0.001), and LAS(OR, 1.73; 95% CI, 1.15–2.59; p = 0.008), while NPC1L1 (Niemann-Pick C1-like protein) -mediated LDL-C levels were associated with a higher risk of small vessel stroke(SVS)(OR, 6.10; 95% CI, 2.13–17.43; p = 0.0008).The SMR revealed that expression of PCSK9 was associated with risk of AS(OR, 1.15; 95% CI, 1.03–1.28; p = 0.01), AIS(OR, 1.02; 95% CI, 1.14–1.29; p = 0.03), cardioembolic stroke(CES)(OR, 1.28; 95% CI, 1.01–1.61; p = 0.04). And, a significant association was found between the expression of NPC1L1 and the risk of SVS (OR, 1.15; 95% CI, 1.00–1.32; p = 0.04). Conclusions: We cautiously find that LDL-C and apoB was positively correlated with LAS. These findings suggest that the reducing LDL-C levels could be an effective prevention strategy for reducing the risk of stroke.